Pengaruh Literasi Anti-Fraud dan Etika Akademik terhadap Perilaku Pencegahan Fraud Mahasiswa - Bambang Arianto; Erliana Erliana (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis, Universitas Jenderal Soedirman, Indonesia, 2025)
This study aims to examine the effect of anti-fraud literacy and academic ethics on students’ fraud prevention behavior. This issue arises from the increasing incidence of various forms of academic fraud in higher education institutions, such as plagiarism, examination cheating, and manipulation of academic data. Fraud prevention in the academic environment does not solely depend on institutional regulations but is also influenced by individual student factors, particularly the level of anti-fraud literacy and academic ethics. This research employs a quantitative approach using a survey method by distributing questionnaires to 90 university students in the Serang City, Banten region. The research data were analyzed using Structural Equation Modeling Partial Least Squares (SEM-PLS) with SmartPLS software to test the relationships among constructs as well as the validity and reliability of the measurement model. The results indicate that anti-fraud literacy has a positive and significant effect on students’ fraud prevention behavior. Furthermore, academic ethics is also proven to have a positive effect on students’ fraud prevention behavior.